KEARIFAN LOKAL IBEIYA DAN KONSERVASI ARSITEKTUR VERNAKULAR PAPUA BARAT - Hematang, Yashinta I.P.; Setyowati, Erni; Hardiman, Gagoek (Indonesian Journal of Conservation, 2014)
Ibeiya is a Kaki Seribu Traditional House of Moile Tribe who lives on the highlands of Arfak Mountains, Minyambouw district. Along with the time and globalization, the existences of the local culture have been shifted. This research is conducted in order to make the Ibeiya being documented. Moreover, it is conducted to increase the local wisdom which is contained on this establishing traditional house. This research is very useful for the academic learning, the architecture study, the government complements and especially for the society which is located on the tropical mountains having a unique climate. It has a cold climate although its location on the tropical climate. The purpose of this research is to enrich the knowledge of traditional house of nusantara that was wisely designed by our ancestor.The Arfak Mountains is new regency that has just been existed. Therefore, this research is expected to be able to give a rewarding input for the establishing building on this new regency in the future. Moreover, it can create a new concept of building that care about the ecological concept and the local wisdom which is owned by the Arfak Tribe in the future.Keywords: traditional house, tropical mountains, local wisdom, ecologyÂ Ibeiya merupakan Rumah Tradisional Kaki Seribu Suku Moile yang hidup di daerah dataran tinggi Pegunungan Arfak, Distrik Minyambouw. Seiring berkembangnya zaman dan arus globalisasi, budaya lokal atau daerah semakin tergeser eksistensinya. Penelitian ini dilakukan agar terdapat dokumentasi ibeiya. Selain itu, untuk mengangkat nilai-nilai kearifan lokal yang terkandung dalam pembangunan rumah tradisional ini dan dapat menjadi pembelajaran bagi akademisi, arsitek, pemerintah, maupun masyarakat khususnya di daerah pegunungan tropis yang beriklim unik, dimana beriklim dingin tetapi berada dalam area tropis. Penelitian ini bertujuan juga agar dapat memperkaya khasanah pengetahuan rumah tradisional nusantara yang secara bijaksana didesain oleh nenek moyang bangsa. Kabupaten Pegunungan Arfak merupakan kabupaten yang baru berdiri. Sehingga, kajian ini diharapkan mampu memberi masukkan bagi pembangunan bangunan gedung pada kabupaten baru ini di kemudian hari. Hingga, dapat tercipta bangunan yang memperhatikan konsep ekologis dan kearifan lokal milik Suku Arfak di kemudian hari.Kata kunci: rumah tradisional, pegunungan tropis, kearifan lokal, ekologis.Â